THE ACTUALIZATION OF THE PHILOSOPHICAL MEANING OF SULAPA EPPA IN CHOOSING LEADERS IN BUGIS SOCIETY - Ali Said; Ahmad Zuhry Amir; Achmad Musyahid; Andi Alauddin; Ahmad Arief (JOSH: Journal of Sharia, 2026)
This study aims to examine the actualization of the philosophical meaning of sulapa eppa in choosing leaders in Bugis society. This research is qualitative in nature. The research design is a literature review. The results of this study indicate that the actualization of sulapa eppa in political ethics is inseparable from pangadereng, which is implemented in rapang, specifically discussed in rapang tana. Rapang tana is a norm that regulates the pattern of life of the Bugis people in governing their country, where the Bugis people uphold ethics in politics. Political ethics in Bugis society encompass values and principles that are highly regarded in participating in political life. The following are some of the political ethics commonly applied by the Bugis people. The Bugis people value honor and integrity in politics. They expect politicians to act honestly, fairly, and without corruption. This ethic emphasizes the importance of maintaining reputation and public trust. The Bugis people value fair and just leadership. They expect political leaders to fight for the interests of the community equally and not favor certain groups.